Analysis of Product Innovation and Market Development Strategy in Increasing Sawo Sukatali Business Income - Destiani, Delia Veronica; Hernawati, Dewy; Fauziah, Meilan Nurul; Nurazizah, Sarah Siti; Haeliahwati, Susan (SINTESA, 2024)
This study aims to identify product innovation and market development strategies for processed sapodilla fruit to increase business income. This study uses a qualitative method. The data collection technique in this qualitative research method uses direct interview activities by coming to the research location, then observation to obtain clear information, and documentation is carried out. The results of the study indicate that product innovation and market development strategies play an important role in increasing sapodilla business income. The main challenges include limited storage capacity, price fluctuations, and competition with imported products. Solutions include processed innovation, attractive packaging, effective promotion, distribution expansion, and processing research